Selective organic functionalization of graphene bulk or graphene edges - Quintana, Mildred; Montellano, Alejandro; del Rio Castillo, Antonio Esau; Van Tendeloo, Gustaaf; Bittencourt, Carla; Prato, Maurizio (Chemical communications (Cambridge, England), 2011)
Graphene sheets have been functionalized with a PAMAM dendron, finding that graphene can be efficiently functionalized all over the surface, or only at the edges, depending on the reactions used in the functionalization process.